Cerebral blood flow and gray matter volume covariance patterns of cognition in aging. Issue 12 (17th July 2012) - Steffener, Jason; Brickman, Adam M.; Habeck, Christian G.; Salthouse, Timothy A.; Stern, Yaakov
<x xml:space="preserve">Abstract</x> Advancing age results in altered cognitive and neuroimaging‐derived markers of neural integrity. Whether cognitive changes are the result of variations in brain measures remains unclear and relating the two across the lifespan poses a unique set of problems. It must be determined whether statistical associations between cognitive and brain measures truly exist and are not epiphenomenal due solely to their shared relationships with age. The purpose of this study was to determine whether cerebral blood flow (CBF) and gray matter volume (GMV) measures make unique and better predictions of cognition than age alone. Multivariate analyses identified brain‐wide covariance patterns from 35 healthy young and 23 healthy older adults using MRI‐derived measures of CBF and GMV related to three cognitive composite scores (i.e., memory, fluid ability, and speed/attention). These brain‐cognitive relationships were consistent across the age range, and not the result of epiphenomenal associations with age and each imaging modality provided its own unique information. The CBF and GMV patterns each accounted for unique aspects of cognition and accounted for nearly all the age‐related variance in the cognitive composite scores. The findings suggest that measures derived from multiple imaging modalities explain larger amounts of variance in cognition providing a more complete understanding of the aging brain. Hum Brain Mapp 34:3267–3279, 2013. © 2012 Wiley Periodicals, Inc.